(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The article presents an experimental investigation of the possibility for using the finite elements method (FEM) for definite the frequency of cross vibrations to the barrel of the small arm. To achieve the goals of the investigation a model of a real barrel with software product based on the method of the final elements is created. An experimental investigation with real shooting is done and statistics hypothesis checking is executed.